PERAN FILSAFAT KEILMUAN DALAM PERKEMBANGAN ILMU PENGETAHUAN - Ulfa, Dina Maria; Fadhilah Nur Oktaviani; Agung Winarno (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Philosophy of science plays a crucial role in providing a conceptual foundation for knowledge development, particularly by studying ontology, epistemology, and axiology. This study aims to explore how the philosophy of science contributes to the advancement of knowledge, including its role in establishing ethical and moral frameworks to address technological and social challenges. Using descriptive analysis based on a literature review, this research reveals that the philosophy of science functions as a theoretical framework and a critical control tool for applying science in society. The findings emphasize the importance of interdisciplinary integration and the development of new paradigms to address global challenges. With its holistic approach, the philosophy of science is shown to guide the evolution of knowledge to remain relevant, ethical, and positively impactful for civilization.